Non-contact surface thermal deformation measurement based on chromatic confocal sensor - Mao, Xiaoxiao; Xing, Zhiming; Zhao, Bin; Sun, Fei; Gao, Xiumin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Chromatic confocal sensors are widely used in chip processing, high-precision instrument manufacturing, industrial testing and other fields because of high-precision displacement recognitioncapabilities. This research combines a chromatic confocal device with resistance temperature detector for dynamic deformation measurement of heating pipeline. The system is suitable for the measuring range of 300 µm and resolution can reach 0.3 µm. Using finite element method to simulate thermal deformation of aluminium with a thickness of 2 mm, and obtaining simulation trends and results. The end face of aluminium is heated continuously and uniformly in experiment, recording the data of spectral, laser triangular displacement sensor, and temperature sensor at 10°C intervals, respectively. And using Gaussian fitting algorithm to obtain spectral peaks, the corresponding thermal deformation is obtained through the relationship between wavelength and axial displacement. The results show that the experimental data of the chromatic confocal sensor is consistent with the laser triangular displacement sensor basically, with a maximum standard deviation of 1.06. In addition, simulation and experimental trends are consistent.
Optica Applicata, Vol. 54, 2024, nr 2, s. 245-257
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; chromatic confocal sensor; laser triangular displacement sensor; thermal deformation measurement; finite element method